Legal considerations of Military judges regarding drug abuse by TNI - Hartawan, Daesyifa Bunga; Andrisman , Tri; Husin, Budi Rizki (Penerbit Goodwood, 2024)
Purpose: This research aims to determine the basic considerations of military judges in giving decisions on case no. 51-K/PM I-04/AD/VII/2021. Apart from that, it aims to analyze whether the judge in handing down the decision has considered substantive justice or not. Methodology/approach: This research is a type of Normative Juridical and Empirical Juridical research. Normative Juridical research is carried out based on legal materials such as legal theory, legal principles and legislation related to research. Results/findings: Based on the results of the research and discussion, it is clear that the basis for military judges legal considerations regarding TNI members who abuse narcotics consists of juridical and non-juridical considerations. Limitations: The Panel of Judges has not implemented substantive justice, this is because some TNI who were dismissed from military service due to narcotics abuse did not take part in a medical rehabilitation program, so that when they returned to society, their condition had not fully recovered from narcotics dependence. Contribution: The judge's decision should create order and legal certainty and fulfill a sense of justice towards TNI members who abuse narcotics. Military judges should consider social and medical rehabilitation of TNI members who abuse narcotics. This rehabilitation action is also in line with a number of decisions of the Supreme Court of the Republic of Indonesia which ordered the rehabilitation of TNI soldiers who abuse narcotics and considered imposing additional penalties in the form of dismissal from military service.